2021
DOI: 10.3390/ijms22084015
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inactivation Strategy of Staphylococcus aureus Using Decay-Accelerating Factor and the Response of Infected HaCaT Cells

Abstract: Staphylococcus aureus is a species of Gram-positive staphylococcus. It can cause sinusitis, respiratory infections, skin infections, and food poisoning. Recently, it was discovered that S. aureus infects epithelial cells, but the interaction between S. aureus and the host is not well known. In this study, we confirmed S. aureus to be internalized by HaCaT cells using the ESAT-6-like protein EsxB and amplified within the host over time by escaping host immunity. S. aureus increases the expression of decay-accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the current study, the use of scRNA-seq led to some surprising observations such as the changes occurring in the B cell compartment, especially CD55+ B cells, because ConA is a polyclonal T cell mitogen. CD55, also called Decay Accelerating Factor, is a regulatory protein involved in complement activation and has been shown to be modulated in many infections and diseases (66)(67)(68)(69). An increase in the surface expression of CD55 has been associated with inhibition of complement system activation (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the use of scRNA-seq led to some surprising observations such as the changes occurring in the B cell compartment, especially CD55+ B cells, because ConA is a polyclonal T cell mitogen. CD55, also called Decay Accelerating Factor, is a regulatory protein involved in complement activation and has been shown to be modulated in many infections and diseases (66)(67)(68)(69). An increase in the surface expression of CD55 has been associated with inhibition of complement system activation (69).…”
Section: Discussionmentioning
confidence: 99%
“…CD55, also called Decay Accelerating Factor, is a regulatory protein involved in complement activation and has been shown to be modulated in many infections and diseases (66)(67)(68)(69). An increase in the surface expression of CD55 has been associated with inhibition of complement system activation (69). It has been reported that a decrease in the mean fluorescence intensity of CD55 was observed in T and B lymphocytes from systemic lupus erythematosus patients, implicating this marker as a possible player in lymphopenia (70).…”
Section: Discussionmentioning
confidence: 99%
“…During infection, S. aureus induces apoptosis in a wide range of target cells as a means of invading tissues and antagonizing host immune defenses [22]. Cell death, such as apoptosis and necrosis, is also used when S. aureus is released from keratinocytes [23]. S. aureus produces apoptotic virulence factors, including potent toxins such as α-toxin and enterotoxins and superantigens [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely overcome during pathogenic candidal growth since the presence of C. albicans is known to significantly enhance the presence of S. aureus on the tongue of immunocompromised mice [ 10 , 11 , 13 ]. Similar to C. albicans, S. aureus has developed various mechanisms to avoid complement mediated killing, including the inhibition of MAC formation [ 100 ], inhibition of the classical and lectin pathways [ 101 ], and the utilization of various extracellular proteases which efficiently degrade crucial complement factors [ 102 ]. Since both organisms possess mechanisms to inhibit the complement system, their inhibitory potency likely adds up during co-infection.…”
Section: Extra-epithelial Oral Immunitymentioning
confidence: 99%